Silent Monosodium Urate Crystal Deposits Are Associated With Severe Coronary Calcification in Asymptomatic Hyperuricemia: An Exploratory Study - Andrés, Mariano; Quintanilla, María‐Amparo; Sivera, Francisca; Sánchez‐Payá, José; Pascual, Eliseo; Vela, Paloma; Ruiz‐Nodar, Juan‐Miguel (Arthritis & rheumatology (Hoboken, N.J.), 2016)
Objective To evaluate the association between monosodium urate (MSU) crystal deposits in patients with asymptomatic hyperuricemia and the severity and extension of coronary artery disease (CAD). Methods In this cross‐sectional study, consecutive inpatients with a non–ST elevation acute coronary event and asymptomatic hyperuricemia (serum uric acid concentration of ≥7.0 mg/dl) or normouricemia (serum uric acid concentration of <7.0 mg/dl) were enrolled. In patients with asymptomatic hyperuricemia, the presence of MSU crystals was determined by ultrasound evaluation of both knees and first metatarsophalangeal joints and by compensated polarized light microscopy. CAD was assessed by coronary angiography, and the following variables were considered: 1) the presence of moderate‐to‐severe coronary artery calcification, 2) the number of significant coronary stenoses, and 3) the presence of multivessel disease. The association between variables indicating the severity of CAD and the presence of MSU crystals was analyzed by multivariate regression. Results One hundred forty patients were enrolled. After ultrasonography and microscopic analyses were performed, the patients were classified as having normouricemia (n = 66), asymptomatic hyperuricemia alone (n = 61), and asymptomatic hyperuricemia with MSU crystals (n = 13). The prevalence of moderate‐to‐severe coronary calcification was significantly higher in the patients with asymptomatic hyperuricemia with MSU crystals compared with patients with asymptomatic hyperuricemia alone and patients with normouricemia (P = 0.003). An independent association was observed between the presence of moderate‐to‐severe calcification and asymptomatic hyperuricemia with crystals (odds ratio 16.8, P = 0.002). No significant association was observed for the other variables. Conclusion Silent deposition of MSU crystals in patients with asymptomatic hyperuricemia was associated with more severe coronary calcification, which suggests more severe CAD in relation to crystal deposition.